An Experiment of Animation Development in Hypertext Preprocessor (PHP) and Hypertext Markup Language (HTML) - Ahmad, Danial Kafi; Ahmad, Mariam Farida; Ahmad, Mohd Nazmi; Ahmad, Abdullah Syafiq (International Journal of Scientific Research in Computer Science and Engineering, 2020)
Animation is considered as an important element in Computing Industry as well as in Computing Education. This research and experiment were about the development of light animation program which implemented the usage of few web pages to create animation i.e. combination of few different images which were created using combination of Hypertext Preprocessor (PHP) and Hypertext Markup Language (HTML) scripting language. The developed program visualized the animation of a movement of an object which last for approximately TWO (2) seconds per cycle. It was found that the animation is depending on the connection speed as the web page require buffering and jumping (linking) to other web pages. This research demonstrated the usage of basic animation concept which deployed in digital means. Even so, in general, it may be considered that they were not many of animation created using both combination of PHP and HTML, especially in the education aspect. The experiment was conducted by developing a code snippet which integrate the usage of static image. This is as to reflect the usage of basic animation concept to create motion towards the human vision. There were few test cases of program requirement created in order for the code to be executed for testing.